Endometrial mRNA expression of key inflammatory genes and progesterone receptor in uterine tissue of bitches with endometritis - García Mitacek, María Carla (2023)
Our study aimed to evaluate the gene transcription of Cyclooxygenase 1 (COX1), cytokines (Interleukin 6 [IL6], Interleukin 8 [IL8], and Leukemia inhibitory factor [LIF]), and Progesterone receptor (PR) in clinically healthy bitches with normal endometrium and with endometritis without the presence of cystic endometrial hyperplasia. Forty-eight mixed breed bitches in dioestrus were used. Uterine biopsies were collected for diagnosis (normal endometrium [n = 15], and endometritis [n = 30]). Three samples were excluded from the study (two bitches with cystic endometrial hyperplasia and one bitch with atrophy). Samples were collected by cytobrush to quantify mRNA by qPCR. Data were analyzed using a generalized mixed model. COX1, IL6, and IL8 mRNA expression in bitches with endometritis was significantly higher than in normal endometrium (p=0.0002, p=0.002, and p=0.003, respectively). In contrast, LIF and PR mRNA expression in bitches with endometritis was significantly lower than in normal endometrium (p=0.006 and p=0.001, respectively). IL6 (AUC 0.67) was the most favorable biomolecular marker for predicting endometritis in bitches. There was an evident change in the mRNA expression of COX1, cytokines, and PR in clinically healthy bitches with normal endometrium and endometritis without cystic endometrial hyperplasia. These results suggest that biomolecular markers such as COX1, IL6, IL8, LIF, and PR could help diagnose endometritis in the bitch.